Efficacy and safety of vonoprazan-amoxicillin dual therapy versus bismuth-containing quadruple therapy for patients with Helicobacter pylori infection: a meta-analysis - Li, Xiao; Jiang, Cheng; Su, Yuwen; Gao, Ruiyun; Yang, Peijun; Qin, Yuechen; Zou, Yue; Liang, Weiming; Quan, Jieru; Pan, Liying (Frontiers in Microbiology, 2025)
IntroductionThis meta-analysis aims to compare the efficacy and safety of vonoprazan-amoxicillin (VA) dual therapy in comparison to bismuth-containing quadruple therapy (BQT) for patients with Helicobacter pylori (H. pylori) infection.Materials and methodsFour databases (PubMed, Embase, Web of Science, and Cochrane Library) were searched published from establishment of database to June 1, 2024, for articles studying VA dual therapy compared to BQT for patients with H. pylori infection. Meta-analyses of eradication rates, adverse events, compliance and cost were preformed.ResultsA total of 17 studies were included for meta-analysis. Compared with BQT, VA increased the incidence of H. pylori eradication rate, with significant difference under the ITT analysis (86.9% vs. 80.4%, RR = 1.07, 95% CI: 1.01–1.12, p = 0.01) but there no significant difference under the PP analysis (90.7% vs. 86.5%, RR = 1.03, 95% CI: 0.99–1.08, p = 0.13). Besides, VA significantly increased compliance (RR = 1.03, 95% CI: 1.01–1.05, p < 0.01) and decreased the occurrence of total adverse events (27.0% vs. 11.5%, RR = 0.43, 95% CI: 0.37–0.51, p < 0.01). Furthermore, VA has lower cost compared to BQT.ConclusionOur findings indicated that VA dual therapy provided a higher eradication rate, enhanced compliance, decreased adverse events, and lowered cost relative to BQT for patients with H. pylori infection.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42024576738, identifier CRD42024576738 (PROSPERO).